The relationship of learning styles to the intelligence of the students of the College of Basic Education (Journal of the College of Basic Education, 2023)
Some of those interested in the educational field claim that educational institutions have failed to developstudents’ learning abilities, and this claim is based on several pillars, including exposing studentseducational methods that deny their abilities and preparations and ignore their learning methods because ofTeachers' ignorance of learning styles and their lack of knowledge of how to deal with each style properlyEnables them to achieve the educational goals to the maximum extent of the students' ability and potential.Finding appropriate teaching methods does not come without knowing the students' learning patterns.Many educational and psychologists have highlighted the importance of the teacher organizing the conditions oflearning related to the learner and the surrounding environmental conditions. These conditions include the learner's abilities.his mental and physical conditions, his social and emotional conditions, his personality and thinking pattern, and what arouses his motivationIt draws his attention and puts him in a state of mental readiness conducive to learning, and all of this requires that the teacherBy adopting an applied practical framework that facilitates the classification of students according to similarities in their learning methods.and their thinking, and this indicates the need to stand on the students’ learning methods and try to organize them.Within specific patterns that are easy to deal with by the teacher, which makes it easy to find out the methods ofAppropriate education, which is what all societies need in light of the new world order that constitutesCompetition in the field of science and creativity is an essential pillar of urbanization and national sovereignty.